Advances in therapy of breast cancer: overexpression and therapeutic implications of targeting human epidermal growth factor receptors - Bhalla, Amit (International Journal of Basic & Clinical Pharmacology, 2019)
The human epidermal growth factor receptor 2 (HER2) ERbb2 gene is amplified in approximately 25% of breast cancers. Characteristics of HER2-amplified tumors include increased proliferation rates and a propensity for distant metastasis. The discovery of overexpression of HER2 in a subset of breast cancers was an important milestone in our understanding of the biology of the disease. This paved the way for the discovery of trastuzumab, a humanized monoclonal antibody targeting HER2. Trastuzumab is the foundation of treatment of HER2- positive breast cancers, demonstrating dramatic responses in patients with metastatic disease. Recent advances in our understanding of the interaction between HER2 and other members of the epidermal growth factor receptor family have led to the identification of newer agents, resulting in the expansion of the clinical armamentarium of available agents for the treatment of HER2-positive tumors. The biology of the ERbb receptor family, the use of HER2-targeted agents in breast cancer, and the advances in anti-HER2 agents that are currently in clinical development are reviewed here.